PELATIHAN PENERAPAN APLIKASI AUGMENTED REALITY PENGENALAN BAHASA ISYARAT DI SLB NEGERI LURAGUNG DESA CIRAHAYU KECAMATAN LURAGUNG KABUPATEN KUNINGAN PROVINSI JAWA BARAT - Sugiharto, Tito; Priguna, Gentur (Empowerment : Jurnal Pengabdian Masyarakat, 2019)
Abstract Community Service Activities/ Kegiatan Pengabdian Kepada Masyarakat (PKM) with the theme "Training on Application of Augmented Reality Application for Sign Language Introduction in SLB Negeri Luragung, Cirahayu Village, Luragung Subdistrict, West Java Province" has a target of Teachers and Students in schools. The problems faced by partner institutions in community service activities include: the learning process of Sign Language in SLB Negeri Luragung still uses book media as the main media in learning. Besides learning media provided at SLB Negeri Luragung also by reading utterances through lip movements combined with cued speech. In addition, the problem faced by teachers in schools for deaf students is the development of language in its function as a means of communication, both verbally and signaling. Language development and speech go together with hearing acuity. Due to limited hearing, deaf students do not occur in the process of imitation of sound, imitation process is only limited to visual imitation. Therefore we need an alternative media for learning that can help the process of visual imitation. The absence of additional alternative learning media used in SLB Negeri Luragung that can help teachers and students in helping students communicate and learn easily becomes a special goal in community service activities. Community service aims to train and implement Augmented Reality Technology as an innovation and development of sign language learning media applications in SLB Negeri Luragung. Deaf students in SLB Negeri Luragung are expected to be able to more easily and quickly understand the sign language learning process with the application of learning based on Augmented Reality. Keywords: Augmented Reality, Deaf, Learning, SLB Negeri Luragung, Sign Language